Product Diversity, Demand Structures and Optimal Taxation - Roland Winkler; Vivien Lewis (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies optimal taxation in a general equilibrium macro model with endogenous entry. We compare the constant elasticity of substitution (CES) model to three alternative demand structures: oligopolistic competition in prices, oligopolistic competition in quantities, and translog preferences. Our economy is characterized by two distortions: a labor distortion due to the misalignment of markups on goods and leisure, and an entry distortion due to the misalignment of the consumer surplus effect and the profit destruction effect of entry. The two distortions interact in determining the wedge between the market-driven and optimal level of product diversity. We show how optimal labor and entry taxes depend upon the prevailing demand structure, the nature and size of entry costs, and the degree of substitutability between goods.
Keywords: E22; E61; H21; 330